Eat or Be Eaten: A Theory of Mergers and Firm Size - GORTON, GARY; KAHL, MATTHIAS; ROSEN, RICHARD J. (Journal of Finance, 2009)
ABSTRACT We propose a theory of mergers that combines managerial merger motives with an industry‐level regime shift that may lead to value‐increasing merger opportunities. Anticipation of these merger opportunities can lead to defensive acquisitions, where managers acquire other firms to avoid losing private benefits if their firms are acquired, or “positioning” acquisitions, where firms position themselves as more attractive takeover targets to earn takeover premia. The identity of acquirers and targets and the profitability of acquisitions depend on the distribution of firm sizes within an industry, among other factors. We find empirical support for some unique predictions of our theory.